Mental Nerve Paraesthesia: A Report of Two Cases Associated with Endodontic Etiology - Neeta Patel; Akshayraj Langaliya; Shikha Kanodia; Aravind Kumbhar; Aastha Buch; Aarshvi Shah; Himani Bhatt; Drashti Panchal; Sharan Shah; Jinali Shah (Hindawi Limited, 2021)
Paraesthesia of the mental nerve can occur due to various etiological factors. Rarely, dental infections can cause paraesthesia. However, this article discusses two cases of endodontic etiology in the mental nerve region as a causative factor for paraesthesia. In the first case, the patient had severe pain localized to his right mandible, with numbness of his lower lip. Endodontic treatment led to quick regression and resolution of paraesthesia. In the second case, a patient who was referred for retreatment of a mandibular second premolar infection developed profound paraesthesia in the region of the mental nerve distribution following prior therapy. Possible mechanisms responsible for periapical infection-related paraesthesia are discussed here. CBCT imaging may be useful in the diagnosis and management of such conditions.